Electronic Properties of Optically Switchable Photochromic Diarylethene Molecules at the Interface with Organic Semiconductors. Issue 7 (15th February 2017) - Wang, Qiankun; Frisch, Johannes; Herder, Martin; Hecht, Stefan; Koch, Norbert
Abstract: Light‐switching‐induced changes in the electronic properties of photochromic diarylethene, i.e., 1, 2‐bis(2‐methyl‐5‐ p ‐tolylthiophen‐3‐yl)cyclopent‐1‐ene (DAE1), thin films at interfaces to a gold electrode and two polymer semiconductors are investigated by direct and inverse photoelectron spectroscopy. The photoisomerization is achieved by in situ irradiation of ultraviolet and visible light. Efficient and reversible switching between the open and closed isomers of DAE1 is evidenced at all interfaces, with profound impact on the energy‐level alignment. The frontier occupied level of DAE1 changes by 0.8 eV with respect to the Au Fermi level upon switching. Corresponding sizable changes in the electron and transport level offsets between the two polymers and DAE1 in its open and closed form are determined. This gives rise to fundamentally different functionality of these interfaces in terms of charge transport. Our study proves the viability of light‐controlled energy‐level manipulation at various interfaces in photoswitchable opto‐electronic devices. Abstract : Light in control : The photoisomerization of a photochromic diarylethene (DAE1) is achieved by in situ irradiation of ultraviolet ( λ =365 nm) and visible light (λ>450 nm). Efficient and reversible switching between the open and closed isomers of DAE1 is evidenced at all interfaces, with a profound impact on the energy level alignment.